Flood vulnerability assessment using data envelopment analysis – the case of Narmada river basin districts in central India - Shefali Dubey Pathak (IWA Publishing, 2021)
This paper presents a data envelopment analysis (DEA)-based framework for estimating the flood vulnerabilities in river basins. The methodology has been exemplified for the 21 districts of the Narmada river basin in central India. Sensitivity and adaptive capacity indicators have been identified and used for the development of the Flood Vulnerability Index (FVI). DEA-based study was employed to assess the Scale Efficiencies and the Returns to Scale and insights drawn from the analysis have been discussed in the context of policy and planning related to reduction of flood vulnerabilities. Cluster analysis has also been deployed to classify districts in terms of flood vulnerabilities. Results from the flood vulnerability assessment model case study indicate that 76% of the districts in the Narmada river basin remain highly vulnerable to flood-risk, while the socio-economic parameters and physical sizes of districts and their resources play a crucial role. HIGHLIGHTS The paper provides a framework for assessment of flood vulnerabilities using the mathematical tool from operations research.; The generic framework is illustrated by a case study from India.;